Hepatic Lipid Accumulation and Dysregulation Associate with Enhanced Reactive Oxygen Species and Pro-Inflammatory Cytokine in Low-Birth-Weight Goats - Tingting Liu; Rui Li; Nanjian Luo; Peng Lou; Sean W. Limesand; You Yang; Yongju Zhao; Xiaochuan Chen (Animals, 2022)
Occurrence of low birth weight (LBW) is a major concern in livestock production, resulting in poor postnatal growth, lowered efficiency of feed utilization, and impaired metabolic health in adult life. In the southwest region of China, birth weight of indigenous strains of goats varies seasonally with lower weights in summer and winter, but the metabolic regulation of the LBW offspring is still unknown. In this study, by comparing LBW goats to normal birth weight group, we examined hepatic lipid content in association with regulatory mechanisms. Histological studies showed higher microvesicular morphology in the liver of LBW goats in accompany with a significantly higher level of hepatic free fatty acids, total triglycerides, and cholesterols. Lipid metabolism impairment, increased oxidative stress, and inflammation were observed by transcriptome analysis. Meanwhile, Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation further demonstrated lipid peroxidation, antioxidant pathway, and pro-inflammatory response involved in the hepatic lipid dysregulation from LBW group. Therefore, dysregulations of hepatic lipid metabolism, including fatty acid biosynthesis and degradation, lipid transportation, and oxidative stress, played important roles to contribute the lipid accumulation in LBW goats. Moreover, due to impaired antioxidant capacity, the oxidative damage could interact with persisting pro-inflammatory responses, leading to a higher risk of liver injury and metabolic syndromes in their adult life.